Relationship Between the Reaction Time and EEG Parameters During Judgments on the Correspondence of Delayed or Simultaneously Presented Images of Two Models - Ishikura, T. (Нейрофизиология, 2016)
This study examined how judging whether the poses of two figures are the same in tasks with delayed and simultaneous image presentation affects the participants’ reaction times and electroencephalograms (EEGs). Eighteen university students performed a delayed task, in which an image of a doll was first presented for 3 sec followed by a second image of the doll, and a simultaneous task, in which images of two dolls were presented on the left and right sides of the monitor at the same time. The dolls were shown from the front and rear angles. The participants were instructed to judge whether the images were the same as accurately and quickly as possible, and the reaction times were recorded. EEG signals were recorded from Fp1, Fp2, F3, F4, C3, C4, P3, and P4. The reaction times in the delayed task were found to be shorter those in the simultaneous task, and that these times for the 0° condition were shorter than for the 180° condition. The amplitudes of EEG responses at Fp1 and Fp2 were larger than those at other electrodes, and that responses in the right hemisphere during the 180° condition and the delayed task within the α1 frequency band were smaller than the responses at other electrodes. These results indicate that cerebral activity in the frontal region of the right hemisphere is associated with the judgment of correspondence or non-correspondence in spatial compatibility tasks. Ми досліджували, яким чином вирішення питання про ідентичність/неідентичність поз тест-фігур, зображення яких представлялись одночасно або з часовою затримкою, впливає на латентний період реакції тестованого суб’єкта та параметри ЕЕГ. 18 студентам університету пропонували «затримане» тест-завдання, в якому тест-об’єкт (зображення антропоморфної фігури, ляльки) пред’являвся на 3 с, після чого із затримкою пред’являлося друге зображення, або «одночасне» завдання, в якому два зображення ляльок пред’являлись одночасно на двох половинах екрану монітора. Тест-зображення ляльок показувалося спереду або ззаду (кути 0 або 180 град). Тестованим пропонувалося максимально точно та швидко вирішити, чи ідентичні дані зображення; при цьому вимірювали час реакції. Сигнали ЕЕГ відводили від локусів Fp1, Fp2, F3, F4, C3, C4, P3 та P4. Виявилося, що час реакції при реалізації «затриманого» завдання був коротшим, ніж такий для «одночасного» завдання, і що цей показник для умови 0 град був меншим, ніж відповідне значення для умови 180 град. Амплітуди ЕЕГ у відведеннях Fp1 і Fp2 були вищими, ніж такі в інших відведеннях. ЕЕГ-відповіді в альфа1-субдіапазоні в правій півкулі в «затриманому» тесті для умови 180 град були меншими, ніж аналогічні відповіді в інших відведеннях. Подібні результати вказують на те, що активність у фронтальній зоні правої півкулі асоційована з прийняттям рішення щодо відповідності або невідповідності зображень у завданнях, пов’язаних із встановленням просторового збігу.